Identification and Quantification of Polycyclic Aromatic Hydrocarbons in Tehran Drinking Water by Gas Chromatography-Mass Spectrometry - Baghban1, Mahtab; Mansour Baghahi1, Saeid; Damercheli2, Fatemeh; Akbar Miran Beigi3, Ali (Asian Journal of Chemistry, 2014)
Polycyclic aromatic hydrocarbons are a main group of organic compounds that their monitoring in water recourses is very important because of their side effects such as carcinogenic, genetic and systematic effects on human health. Sources of water pollution with polycyclic aromatic hydrocarbons are oil industries, oil leakage from storage tanks and oil transferring pipe lines, using of fossil fuels, industrial wastewater's disposal, burning and ash of wastes, etc. Due to ecological and environmental importance and also vast spreading of the pollutant resources in many districts of Iran including, monitoring of pollutants is necessary especially in Tehran province in order to ensure the health of water resources. In this study, 16 compounds of polycyclic aromatic hydrocarbons which are listed as potentially-carcinogen agents for human by the United States Environmental Protection Agency (EPA) were determined by gas chromatography-mass spectrometry. The instrument was calibrated in a selected ion monitoring mode (SIM mode) and it was equipped to a 30 m capillary column. In this research five water effluents including Jalalieh, Kan, Tehranpars 1, Tehranpars 2 and Sohanak water treatment plants with several water storage tanks (related to Tehran province water distribution) were studied. The samples were extracted from liquid phase and analyzed by injection to a GC-MS system (Agilent 6890N). The mass spectra indicate that the concentrations of these 16 polycyclic aromatic hydrocarbons compounds are lower than permitted limits of Iranian National Standard (standard number 1053 for drinking water), World Health Organization (WHO) and US.EPA recommendations.